Мотивация литовских библейских топонимов, заимствованных из польского языка - Bilkis, Laimutis (Instytut Języka Polskiego Polskiej Akademii Nauk, 2018)
Lithuanian toponymy includes a number of metaphorical place names deriving from Biblical placenames or Biblical names of people, creatures and phenomena. Some toponyms come from canonicalBiblical onyms or appelatives: names of hill, land, forest and farmstead Alývų kálnas (from the loanwordalyvà ‛olive’), hill names Angel`inė, Angelü˜ kalnẽlis (from the loanword ángelas ‛angel; goodspirit’), land name Galil´ja (Galilee), hill names Golgotà (Golgotha), Siònas (Zion), etc. Other placenames were formed from Biblical names used in dialects and the living language: name of land, hill,forests and meadows Alývų daržẽlis, hill name Aniuolü˜ kálnas (from the loanword ãniuolas ‛angel; goodspirit’), oak name Mƒ˜kos (from the loanword mūkà ‛suffering; figure of crucified Jesus Christ’). Someof these toponymsreflect etymological and/or motivational (semantic) connections with the Polish language:Aniolü˜ kálnas : Lithuanian ãniolas ‛angel; good spirit’ ← Polish anioł, pine name Nazaránskas :Polish Nazareński, village name Sventijánskas : Polish Święty Jan, etc.Motivation for Lithuanian biblical toponyms borrowed from the Polish language is most often associatedwith geographical similarities between denoted items and their biblical counterparts. These mayrefer to location characteristics, properties of the ground (soil), water, relief, configuration and so on.Another motivator is often the sanctity of a denoted item or its surroundings — whether there was oncea sacred object in said location (statue, cross, church, etc.). The motivation is often based on mythologicalor demonological aspects — stories told by the locals of devil hauntings, ghost sightings and such. Socialenvironment and relationship specifics have also been associated with being the basis for motivation.
568 s.
Keywords: toponymics; biblical toponyms; motivation for toponyms; Polonisms